Design of a microfluidic device to simulate the formation of the atheroma plaque - Ríos Ruiz, Itziar; García, Sara Oliván; Martínez Barca, Miguel Ángel; Baquedano, Estefanía Peña (Jornada de Jóvenes Investigadores del I3A, 2019)
The aim of this work is to design a microfluidic device that reproduces the different conditions and parameters of blood flow that appear both in the physiological range of a coronary artery and in the pathological range, in the process of generation and development of an atheroma plaque.